Old school still matters : lessons from history to reform public education in America - Fife, Brian L. (Praeger, 2013)
"Can public schools in America be saved? This book considers theory, current practice, and the common school ideal through a historical lens to arrive at practical suggestions for reforming contemporary public education"--